Development and Organization of the Lamprey Telencephalon with Special Reference to the GABAergic System - Pombal, Manuel A.; Álvarez-Otero, Rosa; Pérez-Fernández, Juan; Solveira, Cristina; Megías, Manuel (Frontiers in Neuroanatomy, 2011)
Lampreys, together with hagfishes, represent the sister group of gnathostome vertebrates. There is an increasing interest for comparing the forebrain organization observed in lampreys and gnathostomes to shed light on vertebrate brain evolution. Within the prosencephalon, there is now a general agreement on the major subdivisions of the lamprey diencephalon; however, the organization of the telencephalon, and particularly its pallial subdivisions, is still a matter of controversy. In this study, recent progress on the development and organization of the lamprey telencephalon is reviewed, with particular emphasis on the GABA immunoreactive cell populations trying to understand their putative origin. First, we describe some early general cytoarchitectonic events by searching the classical literature as well as our collection of embryonic and prolarval series of hematoxylin-stained sections. Then, we comment on the cell proliferation activity throughout the larval period, followed by a detailed description of the early events on the development of the telencephalic GABAergic system. In this context, lampreys apparently do not possess the same molecularly distinct subdivisions of the gnathostome basal telencephalon because of the absence of a Nkx2.1-expressing domain in the developing subpallium; a fact that has been related to the absence of a medial ganglionic eminence as well as of its derived nucleus in gnathostomes, the pallidum. Therefore, these data raise interesting questions such as whether or not a different mechanism to specify telencephalic GABAergic neurons exists in lampreys or what are their migration pathways. Finally, we summarize the organization of the adult lamprey telencephalon by analyzing the main proposed conceptions, including the available data on the expression pattern of some developmental regulatory genes which are of importance for building its adult shape.